1992
DOI: 10.1007/bf01606873
|View full text |Cite
|
Sign up to set email alerts
|

Specific alterations of the basement membrane and stroma antigens in Human pituitary tumours in comparison with the normal anterior pituitary. An immunocytochemical study

Abstract: Our report is the first immunocytochemical study of the principal elements of the basement membrane (BM) and connective tissue in normal and adenomatous human anterior pituitaries. In normal tissues, both the parenchymatous BM limiting the endocrine cell cords and the endothelial BM around the capillaries were continuous and were stained with anti-laminin (LM), anti-type IV collagen (CIV) and anti-fibronectin (FN) antisera. Antiserum to type I collagen (CI) stained the connective tissue only. The same antigens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 10 publications
4
25
0
Order By: Relevance
“…48 However, other studies suggest that it is present but morphologically abnormal. 49,50 For example, although the vascular BM in pancreatic tumors, as identified by collagen IV, laminin, and nidogen immunostaining, outlines blood vessels in a similar fashion to normal tissue, it still shows numerous structural abnormalities. Its association with endothelial cells and pericytes is much looser than in normal vessels.…”
Section: Vascular Bmsmentioning
confidence: 99%
“…48 However, other studies suggest that it is present but morphologically abnormal. 49,50 For example, although the vascular BM in pancreatic tumors, as identified by collagen IV, laminin, and nidogen immunostaining, outlines blood vessels in a similar fashion to normal tissue, it still shows numerous structural abnormalities. Its association with endothelial cells and pericytes is much looser than in normal vessels.…”
Section: Vascular Bmsmentioning
confidence: 99%
“…Our results concerning the normal anterior pituitary connective-tissue cells showed that a,@, is the principal integrin present at their surface and may mediate the interactions of fibroblasts to laminin-1, type-IV and -I collagens, present in the perivascular connective-tissue space (Farnoud et al, 1992. It is noteworthy that the endothelial cells in the normal anterior pituitary express a pattern of integrin subunits (aI, a5, PI) that is much more restricted than that of normal endothelial cells in systemic vessels which harbor a larger panel of integrins, including the a 1 to (Y6, av and to pj subunits (Springer, 1990).…”
Section: Discussionmentioning
confidence: 69%
“…Regardless of their secretory type, pituitary adenomas differ structurally in various respects from normal anterior pituitary tissue. Adenomas lack the parenchymatous basement membranes that delineate the characteristic cord-like structures of the normal gland (Farnoud et al, 1992(Farnoud et al, , 1994b, which might be responsible for the loss of polarity in adenoma cells and the soft consistency of adenoma tissue due to loose attachment of the cells (Racadot et al, 1975). In addition, contrasting with the dense network of sinusoids fed by the portal vasculature in the normal anterior pituitary, adenomas develop a loose array of systemic neovessels which constitutes the framework of the stroma in these tumors (Racadot et al, 1986;Schechter et al, 1988).…”
mentioning
confidence: 99%
“…The inhibitors of angiogenesis are effective in the suppression of growth of the experimental pituitary tumour (43,44), and the levels of angiogenic cytokines VEGF and bFGF are elevated in the peripheral blood of patients with pituitary adenomas (45). However, Gorczyca & Hardy (46) in angiographic studies detected the presence of additional arteries (which were not part of the portal system) in 66% of their patients with microadenomas of this organ, while Farnoud et al (47) observed changes characteristic for increased vasculogenesis in the basal membrane surrounding cells of pituitary tumours in humans.…”
Section: Angiogenesis and Neoplasms Of Endocrine Glandsmentioning
confidence: 99%